Embedded indexing with Word. Part 5 – locators other than page numbers. (1st June 2021) - Greulich, Walter
Abstract : The focus of the fourth part of this series was on the generation of annotations to page references and of functional indexes for ebooks. In the context of ebook indexes, it described how other fields besides the PAGE field can be incorporated into the XE field. This article follows on from that, showing how, by using the STYLEREF field, it is possible to bring other locators into an index as substitutes for page numbers. The decisive factor here is again the shifting method. Only with this method can the locators be integrated into an overall workflow from Word to ebook or from Word to Index-Manager and back. The first four articles in the series can be found in the June, September and December 2020 issues and in the March 2021 issue of The Indexer (38(2), 38(3), 38(4), 39(1)).